PENGEMBANGAN MEDIA PEMBELAJARAN POWER POINT INTERAKTIF PADA MATERI SIKLUS AIR KELAS V SDN 42 PEKANBARU - Ryche; Laili Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
Lack of teacher ability in conveying water cycle material, the media that is often used so far still uses picture media to explain. Interactive power point media has the potential to help students understand the material by involving students in learning to increase students' learning motivation. Therefore, researchers are interested in developing learning media in the form of interactive power points which are expected to help the needs of teachers and students in learning material that is easier to understand. This research is research and development using a 4D model which is simplified into three stages, namely (Define, Design, and Development). The data collection instrument is in the form of a questionnaire given to material experts, media experts and language experts to test validity. The type of data obtained from research results is qualitative data which is analyzed using quantitative data in the form of numerical data and interpreted using assessment criteria guidelines to determine product quality. The results of this research produced an interactive PowerPoint media product that met the very valid criteria with an average score of 98.9% for media experts, 97.9% for material experts, and 87.5% for language experts with very valid criteria.